The role of cooperation in bacterial ecology and evolution - Hao, C (2023)
Bacteria can perform a range of cooperative behaviours, yet the significance of these cooperative behaviours in bacterial ecology and evolution is a burgeoning research area. In this thesis, I use a comparative genomics approach to elucidate the impact of cooperation on bacterial ecological and evolutionary processes. Specifically, I: (i) probe the effects of cooperation on the evolution of bacterial niche breadth; (ii) investigate the relationship between horizontal gene transfer and bacterial cooperation, with a specific emphasis on the interplay between gene connectivity and sociality in determining gene transfer potential. Additionally, I expand the scope by examining how ecological determinants and genomic characteristics shape the evolution of bacterial growth rates. In summary, this thesis offers novel perspectives on bacterial ecology and evolution through the lens of bacterial cooperation.